2010
DOI: 10.1186/1472-6904-10-12
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of combined prolonged-release oxycodone and naloxone in the management of moderate/severe chronic non-malignant pain: results of a prospectively designed pooled analysis of two randomised, double-blind clinical trials

Abstract: BackgroundTwo randomised 12-week, double-blind, parallel-group, multicenter studies comparing oxycodone PR/naloxone PR and oxycodone PR alone on symptoms of opioid-induced bowel dysfunction in patients with moderate/severe non-malignant pain have been conducted.MethodsThese studies were prospectively designed to be pooled and the primary outcome measure of the pooled data analysis was to demonstrate non-inferiority in 12-week analgesic efficacy of oxycodone PR/naloxone PR versus oxycodone PR alone. Patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 28 publications
6
62
0
1
Order By: Relevance
“…This pooled analysis demonstrated that during a 12-week period, PR OXN provided analgesia that was as effective as PR OX alone, as indicated by the noninferiority of PR OXN versus PR OX in mean pain intensity, and a low and comparable use of supplemental analgesic medication in both treatment arms. Of interest, patients receiving PR OXN demonstrated clinically significant improvements in OIC, and there was also a significantly reduced use of laxatives in the first 4 weeks of the study in patients who received PR OXN compared with those who received PR OX alone [18].…”
Section: Pooled Analysismentioning
confidence: 99%
“…This pooled analysis demonstrated that during a 12-week period, PR OXN provided analgesia that was as effective as PR OX alone, as indicated by the noninferiority of PR OXN versus PR OX in mean pain intensity, and a low and comparable use of supplemental analgesic medication in both treatment arms. Of interest, patients receiving PR OXN demonstrated clinically significant improvements in OIC, and there was also a significantly reduced use of laxatives in the first 4 weeks of the study in patients who received PR OXN compared with those who received PR OX alone [18].…”
Section: Pooled Analysismentioning
confidence: 99%
“…These data were taken from a meta-analysis of the safety and efficacy of oxycodone PR/naloxone PR tablets versus oxycodone PR tablets. 21 This comprised two very similar controlled, randomized, double-blind studies undertaken in 119 and 99 centres, respectively, involving 587 patients with moderate-to-severe chronic pain. 16,22 The BFI values at randomization were used to determine symptoms of constipation; subjects who reported fewer than three complete spontaneous bowel movements per week, without the need to strain, fulfilled the opioid-related constipation criterion required by the protocol of the present study and were included in the OIC population.…”
Section: Oic Populationmentioning
confidence: 99%
“…Some experimental and clinical findings suggest that the positive reinforcing effects that lead to opioid abuse are diminished or even absent in individuals with severe chronic pain, making opioid addiction less likely 51,52 . Of note, withdrawal effects have never been documented in RCTs evaluating OXN PR 16,19,20,53 . Additional longterm studies with PR OXN combination in patients with NP are required to better understand the benefits and risk of this treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Naloxone, following oral administration, acts almost exclusively on opioid receptors in the GI tract; due to the extensive first-pass hepatic metabolism, its systemic bioavailability is however very low, without affecting the central analgesic activity of oxycodone. There is robust evidence that PR OXN is effective in reducing OIBD, while maintaining analgesia in patients with chronic pain of noncancer and cancer aetiology -RCTs and post-marketing observations have documented the efficacy and safety of PR OXN combination, with an improvement in bowel function and a substantial reduction in the use of laxatives [16][17][18][19] . Improved QoL and reduced GI events with PR OXN combination may lead to better cost effectiveness compared with oxycodone monotherapy 38 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation